A study on the relationship between individual factor and transfer of training at workplace in SAJ Ranhill Sdn Bhd / Nur Hafizah Mohd Nasir - Mohd Nasir, Nur Hafizah (Faculty of Business and Management, 2018)
A success organization, they must provide training to their employees to improve the knowledge and skill. After the training program, every employee need to transfer their knowledge to workplace that call as transfer of training. However, there is several factors that can effect the transfer of training at workplace. Thus, this research addresses the relationship between individual factor and transfer of training at workplace in SAJ Ranhill Sdn Bhd. Individual factor that include in this study are motivation factor and self-efficacy factor while transfer of training as a dependent variable in this study.